Gastro-oesophageal reflux disease and dental erosions in adults: influence of acidified food intake and impact on quality of life. Issue 7 (July 2016) - Milani, Daiane C.; Venturini, Ana Paula C.; Callegari-Jacques, Sidia M.; Fornari, Fernando
Abstract : Background and aim: Gastro-oesophageal reflux disease (GORD) and dental erosions (DE) have an established association. We assessed whether GORD is associated with DE controlling for acidified food intake and their relationships with quality of life (QOL). Methods: In this cross-sectional study, 419 adult patients who sought dentistry consultation were considered eligible. Patients responded to questionnaires for GORD symptoms, acidified food ingestion and World Health Organization quality of life (WHOQOL Bref), followed by an oral examination, in which DE were characterized according to the Smith & Knight criteria. Results: A total of 417 patients were included (43.8±13.7 years; 68.8% women). There were 143 patients with GORD (34.3%) and 274 controls without GORD. The prevalence of DE was higher in GORD patients compared with the controls (25.9 vs. 17.2%; P =0.041). GORD was associated with DE after adjusting for acidified food intake ( P =0.035), with a prevalence ratio of 1.52 (0.95 confidence interval 1.03–2.22). The WHOQOL Bref score was significantly lower in the presence of GORD [median 17.2 (GORD−DE−) vs. 15.4 (GORD+DE+); P <0.01], irrespective of DE. Conclusion: In adults examined in a referential dentistry centre in South America, DE were prevalent and significantly associated with GORD. This association was independent of the intake of acidified food in our study. Impairment in QOL was observed in GORD patients irrespective of the presence of DE.